Sheltering populists? House prices and the support for populist parties - Ansell, B; Hjorth, F; Nyrup, J; Larsen, MV (University of Chicago Press, 2022)
Populist parties, particularly from the right of the political spectrum, have sharply increased their electoral support in recent years, creating great media and scholarly interest. In this article we suggest that the housing market may have been important in defining who switched to populist voting and where they were located. We build on existing work that connects house prices to “first-dimension politics” of redistribution and classic left-right political identification to argue that house prices might also shape preferences on the “second dimension” of politics: support for populist nationalism versus liberal cosmopolitanism. Using both novel precinct- and individual-level data from Denmark, we show that negative shocks to house prices over the election cycle are strongly associated with shifts to support for the Danish People’s Party, a pattern that has amplified over recent elections. We then turn to corroborate this relationship using local housing data in Sweden, Norway, and Finland.